Impact of hearing rehabilitation programs on presbycusis management: a systematic review and meta-analysis of randomized controlled trials - Zheng, Zhanhang; Qin, Shuhong; Li, Ruilin; Wang, Wenjuan; Wu, Chenxingzi (Frontiers in Aging, 2024)
BackgroundIn the field of audiology, numerous studies have sought to understand and improve hearing rehabilitation programs for older adults afflicted with presbycusis. Despite this, the field lacks uniform standards pertaining to the intervention methods, frequency, and duration of such programs. These discrepancies have led to varying test results and inconsistent findings across multiple studies.ObjectiveThis meta-analysis aimed to evaluate the efficacy of hearing rehabilitation programs in enhancing the utilization of hearing aids among older adults with presbycusis.MethodsWe conducted a comprehensive exploration of PubMed, Embase, Cochrane Library, and Web of Science to identify randomized controlled trials assessing the role of hearing rehabilitation programs for patients with age-related hearing loss. The search period spanned from the inception of each database to September 12, 2024. Outcomes were synthesized using RevMan 5.4 software.ResultsEight studies met the inclusion criteria, involving 598 patients (290 in the intervention group and 308 in the control group). It was observed that hearing rehabilitation programs significantly diminished self-perceived hearing impairment [MD = −5.80, 95% CI = (−8.16, −3.44), p < 0.00001] and negative emotional states [MD = −1.66, 95% CI = (−3.02, −0.29), p = 0.02], while enhancing hearing aid utilization [MD = 0.22, 95% CI = (0.08, 0.36), p = 0.002]. Nonetheless, these programs did not significantly augment patients’ satisfaction with their hearing aids [MD = 0.09, 95% CI = (−0.17, 0.26), p = 0.66].ConclusionHearing rehabilitation programs significantly improve hearing aid outcomes, reduce self-perceived hearing impairment, and alleviate negative emotional states in patients. However, the current body of evidence is insufficient to conclusively indicate that these programs enhance patient satisfaction with daily hearing aid usage.